Giving Aloe Vera Gel (Aloe Vera) As Topical In Burns Treatment - lisdayanti simanjuntak (Science Midwifery, 2022)
Aloe Vera (Aloe Vera) is a plant native to the African continent which is highly rated as a versatile herbal plant that is easy to find and is still used today as a traditional medicine. Aloe Vera (Aloe Vera) has very beneficial functions for the body, one of which is to accelerate wound healing with properties as anti-inflammatory, antiseptic, and increase tissue granulation. The research method used was observational with a cross-sectional survey analytic descriptive research type.